Penerapan Pembelajaran Problem Solving untuk Meningkatkan Motivasi dan Hasil Belajar Siswa SD 060877 Medan - Siti Rahmadhani Siregar; Amir Danis; Sri Ramadhani; Sugito Sugito (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The purpose of this service is to develop an effective problem solving learning model.. The types of subjects in this study were students of SD 060877 Medan. The instruments used consisted of learning achievement test validation sheets, learning achievement tests and student response questionnaires. Data analysis used is descriptive analysis. The results showed that: (1) material validation, stated that the method developed was suitable for use in the field with revisions and valid, (2) based on field trials, it could be declared effective. This is based on: (i) the percentage of classical completeness increased, namely 89.66% of the 29 students who took the test; (ii) achievement of learning objectives (TPK) achieved; (iii) positive student responses; and the percentage of effective study time. The level of increase in student learning outcomes based on the gain score is moderate.